Fatal poisoning in drug addicts in the Nordic countries in 2017. (August 2020) - Simonsen, K. Wiese; Kriikku, P.; Thelander, G.; Edvardsen, H.M.E.; Thordardottir, S.; Andersen, C.U.; Jönsson, A.K.; Frost, J.; Christoffersen, D.J.; Delaveris, G.J.M; Ojanperä, I.
Highlights: Finland had a different drug profile compared to the other countries. Opioids were the main cause of death among fatal poisoned drug addicts in all countries. Cocaine and MDMA deaths increased in all countries. Sweden saw a high number of deaths from fentanyl analogues. New psychoactive substances have emerged in all countries except Iceland. Abstract: This study is the seventh report on fatal poisonings among drug addicts in the Nordic countries. In this report, we analyse data from the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. Data on gender, number of deaths, places of deaths, age, main intoxicants and substances detected in blood were recorded to obtain national and comparable Nordic data, and to allow comparison with earlier studies conducted in 1984, 1991, 1997, 2002, 2007 and 2012. The death rate (number of deaths per 100, 000 inhabitants) was highest in Iceland (6.58) followed closely by Sweden (6.46) and then lowest in Denmark (4.29). The death rate increased in Finland (5.84), Iceland and Sweden and decreased in Denmark compared to earlier studies. The death rate in Norway, which has decreased since 2002, has stabilised around 5.7 as of 2017. Women accounted for 7–23% of the fatal poisonings. The percentage was lowest in Iceland and highest in Finland and Norway. The age range was 14–70 years. The median age (41 years) was highest in Denmark and Norway. The other countries had a median age between 33 and 35 years. Opioids were the main cause of death. Methadone remained the main intoxicant in Denmark, while heroin/morphine was still the main intoxicant in Norway, as was buprenorphine in Finland. However, the picture has changed in Sweden compared to 2012, where heroin/morphine caused most deaths in 2017. Sweden also experienced the highest number of deaths from fentanyl analogues (67 deaths) and buprenorphine (61 deaths). Deaths from fentanyl analogues also occurred in Denmark, Finland and Norway, but to a smaller extent. Over the years, the proportion of opioid deaths has decreased in all countries except Sweden, which has experienced an increase. This decline has been replaced by deaths from CNS stimulants like cocaine, amphetamine and methylenedioxymethamphetamine (MDMA). Cocaine deaths have occurred in all countries but most frequently in Denmark. MDMA deaths have increased in all countries but mostly in Finland. Poly-drug use was widespread, as seen in the earlier studies. The median number of detected drugs per case varied from 4–6. Heroin/morphine, methadone, buprenorphine, cocaine, amphetamine, methamphetamine, MDMA, tetrahydrocannabinol (THC) and benzodiazepines were frequently detected. Pregabalin and gabapentin were detected in all countries, especially pregabalin, which was detected in 42% of the Finnish cases. New psychoactive substances (NPS) occurred in all countries except Iceland.